PERBEDAAN SIKAP DAN AKTIVITASKOLABORATIF SISWA DENGAN MODEL COLLABORATIVE LEARNINGBERDASARKAN GENDERPADA KELAS VII SMP BABUSSALAM PEKANBARU - Yuni Irawati; Darmawati Darmawati; Suwondo Suwondo (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract:This study aims to describe the attitudes and collaborative activities of students with the Collaborative learning model based on gender in class VII Babussalam Pekanbaru. The study was conducted at Pekanbaru Babussalam Middle School in August to September 2019. The population was all students of class VII Babussalam Pekanbaru. The research samples were determined by purposive sampling, namely VII1 male students and VII4 female students. The parameters measured were collaborative attitudes measured by questionnaires and collaborative activities with observation sheets. The research data consisted of primary data and secondary data. The data collected was analyzed descriptively. The instrument used consisted of learning instruments data collection instruments. Collecting data in this study by distributing questionnaires before and after learning. Observation sheet is done during the learning process 5 meetings. The results showed that there were differences in students' attitudes and collaborative activities using Collaborative Learning. The score of the collaborative attitude of the male class before using the Collaborative learning model was 3.18 and the women's class was 3.40. the score of the collaborative attitude of the male class after using the Collaborative Learning model was 3.23 and the women's class was 3.39. The average score of collaborative activity of male students is 3.38 (very high category) and female classes is 3.37 (very high category).Key Words: Collaborative Attitudes, Collaborative Activities, Collaborative Learning, Gender